THE ROLE OF DIGITALIZATION AND DATA INTEGRATION IN PROTECTING WAKAF ASSETS IN EAST KALIMANTAN - Fadhilah, Nurul; Ratulia, Yaya; Norvadewi, Norvadewi (AL-QARDH, 2024)
This research is based on the increasing number of waqf assets that require continuous management and monitoring by the Regional Office of the Ministry of Religion of East Kalimantan Province. Previously, waqf asset management only relied on administrative records in the waqf notebook. With the development of technology, geographic information systems and remote sensing technology are needed to manage and preserve waqf assets effectively. This research aims to explore the role of digitalization and data integration in protecting waqf assets in East Kalimantan.This research uses a qualitative descriptive approach with field research methods. Data was collected through interviews, observation and documentation. Interviews were conducted with several key sources such as the Chair of the Zakat and Waqf Empowerment Team, Functional Religious Counselors, BWI staff, and Religious Affairs Material Compiler at the KUA of Loa Janan District. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The research results show that the Ministry of Religion of East Kalimantan Province has implemented land waqf management practices using a website-based digitalization system called SIWAK (Waqf Information System) as well as cash waqf through QRIS. The data integration system is also used in land waqf through SIWAK. Digitalization and data integration are very helpful in protecting waqf assets from problems such as illegal levies and waqf land disputes. However, the obstacles faced include the waqif's lack of knowledge regarding digital waqf, the lack of financial assistance from the government for socialization of digital waqf, and the nazhir's low understanding of digitalization. This research concludes that the role of digitalization and data integration is very crucial in protecting and managing waqf assets in East Kalimantan, although there are still several obstacles that need to be overcome to optimize this system.